The effect of climate change on electricity needs – A case study from Mediterranean Europe - Hadjinicolaou, Panos; Zachariadis, Theodoros (My University, 2014)
This paper assesses additional electricity requirements and the associated costs in the Mediterranean island of Cyprus by the mid-21st century because of projected anthropogenic climate change, following an interdisciplinary approach that combines climate science with economics. An econometric model of electricity demand is used, in conjunction with climate projections from a state-of-the-art Global Circulation Model with a regional focus on the Eastern Mediterranean. Annual electricity demand is projected to rise by about 6% compared to a ‘no climate change’ case. Although these additional power requirements are not very remarkable on an annual basis, total costs up to 2050, which may exceed 730 million Euros at today's prices, imply that the country may need to forgo one or two years of economic growth in order to cope with extra electricity needs due to climate change. This outlook indicates that a reasonable future energy path in regions with Mediterranean climate would involve substantial deployment of solar-powered electricity generation, which can meet peak load requirements while reducing the country's energy dependence. Moreover, this forecast highlights the need for adaptation to climate change through investments in the improvement of the energy performance of the building stock.
Keywords: Degree-days; Econometric model; Regional climate model; Welfare losses